Syndemic effect of mental illness and substance use on viral suppression among recently-incarcerated, HIV-infected individuals in the CARE+ Corrections study. Issue 10 (3rd October 2018) - Yellin, Hannah; Beckwith, Curt; Kurth, Ann; Liu, Tao; Castonguay, Breana; Patrick, Rudy; Trezza, Claudia; Bazerman, Lauri; Kuo, Irene
ABSTRACT: Few studies on HIV-related syndemics of co-occurring and mutually reinforcing psychosocial conditions have assessed clinical outcomes in criminal justice (CJ)-involved populations. Baseline data from the CARE+ Corrections study were used to quantify co-occurring mental illness and substance use and examine syndemic effects on viral suppression among 106 CJ-involved HIV-infected individuals. Ninety-one (86%) reported a mental illness diagnosis, 30 (28%) reported hazardous alcohol use, and 61 (58%) were drug dependent. Eighteen (17%) experienced all three conditions. Drug dependence was clustered with mental illness (prevalence odds ratio [POR] 3.20, 95% CI 1.01–10.14) and hazardous alcohol use (POR 2.61, 95% CI 1.03–6.56). The association between syndemic score, representing the number of conditions reported by each individual, and viral suppression was not statistically significant, although 86% of participants with none of these conditions were virally suppressed, compared to 56% of those with all three ( p  = 0.56). Mental illness and substance use were concentrated in this sample, indicating a need for integrated care services.